Chilean Aquaculture and the New Challenges: Pathogens, Immune Response, Vaccination and Fish Diversification - Maisey-Munoz, K; Flores-Kossack, C (Academic Press, 2020)
In Chile, the salmon and trout farmed fishing industries have rapidly grown during the last years, becoming one of the most important economic sources for the country. However, infectious diseases caused by bacteria, virus, mycoses and parasites, result in losses of up to 700 million dollars per year for the Chilean aquaculture production with the consequent increase of antibiotic and antiparasitic usage. After 30 years of its first appearance, the main salmon health problem is still the salmonid rickettsial septicaemia (SRS), which together with other disease outbreaks, reveal that vaccines do not provide acceptable levels of long-lasting immune protection in the field. On the other hand, due to the large dependence of the industry on salmonids production, the Chilean government promoted the Aquaculture diversification program by 2009, which includes new species such as Merluccius australis, Cilus gilberti and Genypterus chilensis, however, specific research regarding the immune system and vaccine development are issues that still need to be addressed and must be considered as important as the farm production technologies for new fish species. Based on the experience acquired from the salmonid fish farming, should be mandatory an effort to study the immune system of the new species to develop knowledge for vaccination approaches, aiming to protect these aquaculture species before diseases outbreaks may occur. This review focuses on the current status of the Chilean aquaculture industry, the challenges related to emerging and re-emerging microbial pathogens on salmonid fish farming, and the resulting needs in the development of immune protection by rational designed vaccines. We also discussed about what we have learn from 25 years of salmonid researches and what can be applied to the new Chilean farmed species on immunology and vaccinology. © 2020 Elsevier Ltd